ADAPTATION PATTERNS OF FISHERMEN IN UJUNGALANG VILLAGE, KAMPUNG LAUT DISTRICT, CILACAP TO MAINTAIN THE ECONOMY FAMILIES IN FACING CLIMATE CHANGE - Putri, Raudya Setya Wismoko (Institut Penelitian Dan Pengambangan Mandalika Indonesia (IP2MI), 2024)
Climate change is the main problem faced by fishing communities. The existence of global warming and erratic weather changes are making village fishermen Ujunggalang, Kampung Laut District, Cilacap, cannot determine the arrival of the fish. As coastal communities, fishing communities depend on marine resources to fulfill various kinds of living needs. Based on these problems, the aim of this research is to (1) identify the impact of climate change on the economy and capture fisheries activities, and (2) analyze adaptation patterns and economic strategies carried out by fishermen to overcome the economic impacts caused by climate change. The method used in this research is descriptive research with a qualitative approach. The research was conducted in Ujunggalang Village, Kampunglaut District, Cilacap. The technique for determining research subjects uses purposive techniques. Data collection techniques use interviews and documentation. The technique for checking the validity of the data in this research uses a cross check. Data analysis in this research uses inductive data analysis, including data reduction stages, data categorization, data presentation and conclusion drawing. The results of this research reveal that the impact of climate change is causing fishermen to experience socio-economic problems. In economic matters, the impact of climate change makes fishing communities unable to meet their living needs and vulnerable to low income. Adaptations carried out by fishermen include climate adaptation through